Case Study Business Process Re-Engineering of Supply Chain Activities in Attock Petroleum Limited (APL) (Global Journal of Management and Business Research, 2015)
Organizations in the modern age are being challenged by many difficulties because of the rapid advancements in technology while using old and traditional techniques for the running of their processes. To increase the competitiveness of the organization and to improve the sustainability of the company,the concept of Business process re-engineering is being adopted which involves the radical redesign of process by tossing aside the existing ways and methods.The main objective of this case study is to explore the possibilities for improvement in the processes of Attock Petro;eum Limited(APL) such as supply chain management with the technique of business process reengineering as the traditional approach is affecting the performance of the company. Data has been collected through unstructured interviews from the engineering personnels in the company and from the company website.
Keywords: business process re-engineering; supply chain; attock petroleum limited; vehicle tracking system; auto tank guaging(atg); centralised data acquisition